Cutaneous Squamous Cell Carcinoma Developing from Recessive Dystrophic Epidermolysis Bullosa: A Case Report and an Immunohistochemical Study - Tsukada, Akira (S. Karger AG, 2012)
We describe a 49-year-old Japanese woman with cutaneous squamous cell carcinoma (SCC) developing from recessive dystrophic epidermolysis bullosa (RDEB). Interestingly, immunohistochemical staining revealed dense infiltration of CD163(+) M2 macrophages and numerous Foxp3(+) regulatory T cells (Tregs) around the tumor. Since the contribution of immunosuppressive factors (e.g. TGFβ) to the carcinogenesis of SCC from RDEB was recently reported, our present findings suggest one of the possible contributions of immunosuppressive cells, such as CD163(+) M2 macrophages and Tregs, to the carcinogenesis of SCC from RDEB.